The expediency of using the digital components of the educational platform «Urait» in teaching academic disciplines with dynamic content (on the example of the discipline «Financial accounting») - Brazhnik M. V. (The Topical Issues of the Humanities and Social Sciences: from Theory to Practice, 2023)
the article presents and argues the author's opinion regarding the degree of demand for and expediency of using digital tools and services of the educational platform (EP) «Urait» in the educational process of a higher school in the course of teaching academic disciplines, the content of which is highly dynamic. A classic example of such an academic discipline is «Financial accounting». The introductory part of the article contains a general description of the named academic discipline and a description of the specifics of its teaching. The main content of the article is devoted to the description of the author's experience in using the main digital components of the EP «Urait», such as a flexible course constructor, an interactive assessment system and an online bank of the EP «Urait», as well as free templates for work programs. The final part of the article presents the author's vision regarding the need for a future expansion of the existing functionality of the EP «Urait» and expectations from the emergence of new functions of this platform.
Keywords: образовательный процесс; электронное тестирование; electronic testing; educational process; Юрайт; динамичные учебные дисциплины; цифровые составляющие; конструктор гибких курсов; интерактивное оценивание; шаблоны рабочих программ; модернизация функционала; Urait; dynamic academic disciplines; digital components; flexible course constructor; interactive assessment; work program templates; functionality upgrade